Rare Case of Spontaneous Pneumorrhachis in a Young Male with COVID-19 - Reddy, Vikas; Jajodia, Ankush; Pasricha, Sunil; Goyal, Sumit; Puri, Sunil (Indian Journal of Radiology and Imaging, 2021)
Here we present a rare case of spontaneous pneumomediastinum complicated with pneumorrhachis (PR) in a young man who is a known case of carcinoma rectosigmoid region. Our young male was diagnosed with novel coronavirus disease 2019 (COVID-19) and remained asymptomatic for any respiratory complaints. Though an association of pneumomediastinum has been reported in COVID 19 patients, to the best of our knowledge, this is the first report of PR in a COVID-19 oncological case. The role of a radiologist is to identify this condition as cases reported earlier may have serious neurological consequences. Pursuing the cause can be a diagnostic challenge but it reaps the clinical benefit in the appropriate management.
Keywords: pneumomediastinum; pneumorrhachis; COVID-19